TRADISI REBO WEKASAN DI DESA SUCI KECAMATAN MANYAR KABUPATEN GRESIK (KAJIAN FUNGSI SOSIAL DAN NILAI BUDAYA) - Siti Mahmudah Yanti (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2020)
The purpose of this study was to find out the tradition of Rebo Wekasan and follow the tradition of Rebo Wekasan which was carried out by the Suci KecamatanVillage Manyar District, Gresik. This study used a descriptive qualitative approach proposed by Sugiyono with descriptive analysis and content. The results of this study are expected can contribute scientific thoughts and ideas about the habits of the Javanese people in preserving ancestral culture in this case the Rebo Wekasan Tradition as a cultural preserve in the area. The conclusions of this study are (1) strengthening the faith and piety of Allah SWT because basically the Tradition of Rebo Wekasan which is commemorated in the month of prayer is to ask for protection from Allah SWT because in that month there are many calamities and disasters, (2) the realization of togetherness and harmony between layers an enthusiastic community in commemorating the Rebo Wekasan Tradition by mutual cooperation and shoulder to shoulder in carrying out these activities.